Hawking Radiation of Mass Generating Particles From Dyonic Reissner Nordström Black Hole - Sakallı, İzzet; Övgün, Ali (Springer, 2016)
The Hawking radiation is considered as a quantum tunneling process, which can be studied in the framework of the Hamilton–Jacobi method. In this study, we present the wave equation for a mass generating massive and charged scalar particle (boson). In sequel, we analyse the quantum tunneling of these bosons from a generic 4-dimensional spherically symmetric black hole. We apply the Hamilton–Jacobi formalism to derive the radial integral solution for the classically forbidden action which leads to the tunneling probability. To support our arguments, we take the dyonic Reissner–Nordström black hole as a test background. Comparing the tunneling probability obtained with the Boltzmann formula, we succeed in reading the standard Hawking temperature of the dyonic Reissner–Nordström black hole.
The file in this item is the publisher version (published version) of the article.
Keywords: Hawking radiation; quantum tunneling; dyonic black holes; mass generation